Análisis de las variables integradas que influyen en los procesos de fracturamiento hidráulico con el objetivo de la elección de pozos adecuados para este procedimiento en la Zona Sur del Campo Castilla (2019)
The present degree work studied the variables, operational parameters, geological and petrophysical properties that could possibly influence the success or failure of hydraulic fracturing operations, defined in increased oil production for the Southern Zone of the Castilla Field, which is operated by the national company Ecopetrol SA identifying optimal management ranges for these and thus developing an efficient criteria for selecting candidate wells for future operations.